THE DIGITAL TRANSFORMATION OF AGRICULTURAL BUSINESS - MARKET TRENDS AND CHALLENGES - I. Nencheva; N. Penev (Trakia Journal of Sciences)
Digital transformation is necessary for today's business to remain relevant, competitive and successful. Different technologies bring different benefits to businesses. They help to organize and optimize processes, work more efficiently and create successful products and services.